Assessing the impact of social housing on urban regeneration in South African cities - Noxolo N. Ngema; Ahmed Bokhari; Sijekula L. Mbanga (Frontiers in Sustainable Cities)
Urban regeneration in South Africa addresses historical spatial inequalities and the growing demand for affordable housing. This study examines the impact of social housing on urban regeneration, with a particular focus on the role of the Social Housing Regulatory Authority (SHRA). The SHRA’s mandate to create integrated urban environments with well-located, affordable, and quality rental homes is central to efforts aimed at promoting spatial justice, economic integration, and social development. A qualitative analysis was conducted, involving a review of policy documents, case studies of key social housing projects, and an evaluation of stakeholder reports from provinces such as Gauteng, KwaZulu-Natal, and the Eastern Cape. This multi-method approach facilitated an in-depth understanding of the SHRA’s strategies including regulation, investment, and market transformation and their effectiveness in advancing urban regeneration objectives. The findings indicate that the SHRA has significantly expanded the reach of social housing initiatives by increasing the number of regulated units and delivery agents. Strategic placement of projects in economically vibrant areas has contributed to urban densification and more equitable resource allocation. Moreover, social housing has alleviated financial burdens for low- to medium-income households, improved living conditions, and stimulated economic activity and job creation in the construction and real estate sectors. The study underscores that social housing is a vital instrument for urban regeneration in South Africa. The SHRA’s efforts have disrupted apartheid-era spatial patterns and promoted social mobility by fostering inclusive communities. However, challenges such as construction mafias and rental boycotts persist, highlighting the need for enhanced collaboration among stakeholders to ensure project sustainability. Overall, the integration of social housing initiatives with broader urban regeneration strategies is crucial for achieving spatial integration, economic inclusion, and long-term social development.